Fast assembling microarrays of superparamagnetic Fe3O4@Au nanoparticle clusters as reproducible substrates for surface-enhanced Raman scattering. Issue 32 (16th June 2015) - Ye, Min; Wei, Zewen; Hu, Fei; Wang, Jianxin; Ge, Guanglu; Hu, Zhiyuan; Shao, Mingwang; Lee, Shuit-Tong; Liu, Jian
Abstract : A method featuring fast assembling microarrays of superparamagnetic Fe3 O4 @Au nanoparticle clusters as highly reproducible SERS substrates is reported. Abstract : It is currently a very active research area to develop new types of substrates which integrate various nanomaterials for surface-enhanced Raman scattering (SERS) techniques. Here we report a unique approach to prepare SERS substrates with reproducible performance. It features silicon mold-assisted magnetic assembling of superparamagnetic Fe3 O4 @Au nanoparticle clusters (NCs) into arrayed microstructures on a wafer scale. This approach enables the fabrication of both silicon-based and hydrogel-based substrates in a sequential manner. We have demonstrated that strong SERS signals can be harvested from these substrates due to an efficient coupling effect between Fe3 O4 @Au NCs, with enhancement factors >10 6 . These substrates have been confirmed to provide reproducible SERS signals, with low variations in different locations or batches of samples. We investigate the spatial distributions of electromagnetic field enhancement around Fe3 O4 @Au NCs assemblies using finite-difference-time-domain (FDTD) simulations. The procedure to prepare the substrates is straightforward and fast. The silicon mold can be easily cleaned out and refilled with Fe3 O4 @Au NCs assisted by a magnet, therefore being re-useable for many cycles. Our approach has integrated microarray technologies and provided a platform for thousands of independently addressable SERS detection, in order to meet the requirements of a rapid, robust, and high throughput performance.